Dynamic power management for QoS-aware applications - Marzolla, Moreno; Mirandola, Raffaela (Sustainable computing informatics and systems, 2013)
Reducing the power requirement of large IT infrastructures is becoming a major concern. Energy savings can be achieved with hardware and/or software solutions; in particular, modern CPUs can operate at different power levels that can be selected by software: low power modes reduce energy consumption at the cost of lowering also the CPU processing rate. In this paper we address the problem of reducing energy consumption of a large-scale distributed application subject to Service Level Agreements requiring a maximum allowed response time. Specifically, we propose Energy Aware reconfiguration of software SYstems (EASY), an on-line algorithm for dynamically adjusting the processing speed of individual devices such that the average system response time is kept below a predefined threshold, and the total power consumption is minimized. EASY uses a queueing networks performance model to proactively drive the reconfiguration process, so that the number of individual reconfiguration actions is reduced. We formulate the energy conservation problem as a Mixed Integer Programming problem, for which we propose a heuristic solution technique. Numerical experiments show that the heuristic produces almost optimal results at a substantially lower computational cost. Therefore, EASY can be effectively applied on-line to make a large system energy-proportional.